Stressors Perceived by the Para-clinical Undergraduate Medical Students (Bangladesh Journal of Medical Education, 2018)
Medical curricula are considered as toughest of all curricula of undergraduate professionals. Student faces many stress provoking factors in the academic course. In time identification and adoption of coping strategy can ensure proper achievement of goal of the curriculum. The objective of this prospective study was to find out the nature and intensity of stressors perceived by the mid level medical students (phase II & III) before their summative examination. Regularly passed students of phase II and III undergraduate students of Armed Forces Medical College, Bangladesh were included in the study and the responses were collected in the first week of April 2018 (3 weeks prior to beginning of summative examination). Validated structured set of questionnaire (Medical Student Stressor Questionnaire -MSSQ) was selected for the study and was distributed to the volunteers of target population only. Falling behind in reading schedule, getting poor marks, facing illness or death of the patients and too much restriction in campus were identified as high intensity stressors by the phase II students. On the other hand high workload, not enough scope of medical skill practice, facing illness or death of the patients and too much restriction in campus were identified as high intensity stressors by the phase III students. Intensity of stressors was significantly higher in phase II students than phase III (p=0.000). This study focused the present status of an area. Identification and incorporation of strategies to improve the teaching, learning, evaluation and educational environment are required to help the students to develop stress coping skills in early medical career in order to reduce negative effects of stressors on the future doctors.Bangladesh Journal of Medical Education Vol.9(2) 2018: 3-10